2006
DOI: 10.1007/bf03262555
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a low xylitol-dose on mutans streptococci colonisation and caries development in preschool children

Abstract: The findings do not support a low-dose xylitol tablet program for caries prevention in preschool children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
53
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 23 publications
0
53
0
Order By: Relevance
“…29,30,35 Water was inadequately fluoridated in 1 trial 30 and water fluoridation status was not reported in the other 2. The trials varied with respect to dosing and formulation of xylitol.…”
Section: Xylitolmentioning
confidence: 99%
See 2 more Smart Citations
“…29,30,35 Water was inadequately fluoridated in 1 trial 30 and water fluoridation status was not reported in the other 2. The trials varied with respect to dosing and formulation of xylitol.…”
Section: Xylitolmentioning
confidence: 99%
“…A fair-quality randomized trial (n = 115) of children 2 years of age found xylitol tablets (0.48 g) associated with reduced dmfs increment after 2 years, but the difference was not statistically significant (mean percent reduction 52%, absolute mean reduction in affected surfaces 0.42). 29 One small (n = 37) fairquality randomized trial found xylitol wipes used 3 times per day for 1 year markedly more effective than placebo wipes in reducing caries among children aged 6 to 35 months (reduction in dmfs increment 91%, P , .05). 35 A poor-quality, nonrandomized trial found no effect of xylitol chewing gum (1.33 g) 4 times daily on incidence of caries in 4-year old children in Japan.…”
Section: Xylitolmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly to chewing gum, there are no explicit instructions on the amount the customer is supposed to administer. Considering the benefits of applying xylitol lozenges or hard candies, it is recommended to use them after meals in children over 5 years old [13]. Inulin, present in one of the products, is a naturally occurring probiotic, now gaining popularity.…”
Section: Discussionmentioning
confidence: 99%
“…Another study has shown that xylitol intake of 10.32 g daily in chewing gum yields a significant reduction of SM in resting saliva and dental plaque and that an inverse proportion occurs between the frequency of chewing xylitol gum and bacteria count [12]. Oscarson et al [13] have acknowledged that applying 0.48 g per day and, after 6 months, 0.96 g per day in children over 2 years old has no significant preventive anticarious effect.…”
mentioning
confidence: 99%